What might it take to achieve sustainable development? three contrasting sets of perspectives - Kurian, Priya A. (2017)
Decades after its first articulation, sustainable development continues to hold sway as a powerful concept and policy goal, with its desirability matched only by its elusiveness and contradictions. Often criticised for meaning all things to all people, its promise of combining a commitment to environmental protection with social justice in any search for development has kept it alive in national and international policy and as a focus for academic research. The three books reviewed here explore distinct approaches to sustainable development, moving from addressing the theory and practice of environmental citizenship to rethinking macroeconomic theory for sustainability and challenging the ideology of green growth as contrary to sustainable development. Collectively, they offer insightful analyses and illustrative cases to illuminate the promise and challenges of sustainable development. - Reproduced.
Keywords: Environmental conservation; Social justice; Sustainable development